2021
DOI: 10.1159/000514178
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Routine Medical Checkup and Factors Influencing Use of Routine Medical Checkup among Saudi Students Studying in the USA in 2019

Abstract: Introduction: The few studies that have investigated patterns of routine checkup (hereafter routine checkups) among Saudis have found overall low rates of use. Those studies focused mainly on understanding the influence of individual characteristics on use of routine checkup. Aims: The main purpose of this study was to consider a wider array of factors beyond individual characteristics, including system-based factors, beliefs, attitudes, and satisfaction, and to examine their influence on use of routine checku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
2
13
2
Order By: Relevance
“…Another study found that those significantly more likely to have a routine checkup trusted their primary care providers (PCPs), believed routine checkups were important, were insured, had comorbid conditions, and engaged in physical activity. 6 Unlike El Bcheraoui et al, 5 this study 6 also found that routine checkups were significantly lower among married individuals. Although these studies have contributed to the dearth of knowledge on use of routine checkups among Saudi adults, they focused on characteristics and perspectives of Saudi adult users of healthcare services and did not consider the perspectives of healthcare providers.…”
contrasting
confidence: 50%
See 3 more Smart Citations
“…Another study found that those significantly more likely to have a routine checkup trusted their primary care providers (PCPs), believed routine checkups were important, were insured, had comorbid conditions, and engaged in physical activity. 6 Unlike El Bcheraoui et al, 5 this study 6 also found that routine checkups were significantly lower among married individuals. Although these studies have contributed to the dearth of knowledge on use of routine checkups among Saudi adults, they focused on characteristics and perspectives of Saudi adult users of healthcare services and did not consider the perspectives of healthcare providers.…”
contrasting
confidence: 50%
“…Two survey studies-one involving a nationally representative sample of Saudi adults and the other involving Saudi students studying in the United States of America (USA)-found that three-quarters of the participants had never had a routine checkup. 5,6 A third study reported that 65.7% of Saudis had never had a routine checkup. 7 Accordingly, it is important to understand more about the healthcare-seeking behaviors of Saudi adults.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Alzahrani et al reported that participants who trusted their primary care providers were more likely to perform routine medical checkups. 23 Nonetheless, the association between trusting healthcare providers and the probability of routine medical checkups was not assessed in our study.…”
Section: Discussionmentioning
confidence: 89%